Pre-Service Teachers Problems and Strategies During the Kampus Mengajar (KM) Program - Kinanti, Tri; Triyoga, Arilia (Ahmad Dahlan Journal of English Studies, 2024)
The Kampus Mengajar (KM) Program offers valuable real-world experience despite the challenges that prevent prospective teachers from carrying out their duties. This research aims to find out how prospective English teachers deal with the problems they face when participating in the Kampus KM program. This study is a qualitative study using narrative inquiry method. The subjects of this study were two students majoring in English Educationat a private university in Yogyakarta who had completed four months of KM teaching practice. The instrument used was an interviewguideline. To collect data, the researcher used semi-structured interviews with open-ended questions. The questions in the semi- structuredinterview included the general experiences of participants during the KM program. The researcher used three steps to analyze the data: data reduction, data presentation, drawing conclusions and verification. The results of the study showed that pre-service teachers encountered obstacles during the KM teaching practice period such as lack of teaching media, self-doubt, and lack of student motivation in learning English. This was influenced by several factors such as lack of school facilities, lack of teacher experience in teaching, and differences in motivation and understanding of English between students. Pre-service teachers were required to find strategies to solve problems faced during the teaching practice period; use of games, flash card media, and understanding the material. This affected the self-development of prospective teachers in terms of problem solving and self-confidence.